2009
DOI: 10.1097/coc.0b013e3181967dd0
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Treatment Interruptions Greater Than One Week and Low Hemoglobin Levels (12 g/dL) are Predictors of Local Regional Failure After Definitive Concurrent Chemotherapy and Intensity-Modulated Radiation Therapy for Squamous Cell Carcinoma of the Head and Neck

Abstract: Overall radiation treatment time and pretreatment hemoglobin level were significant predictors for loco-regional failure after definitive concurrent chemotherapy and IMRT for SCCHN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 29 publications
4
53
1
Order By: Relevance
“…[32] McCloskey et al demonstrated that one week deferral of RT in 78 patients with head and neck cancers was an independent prognostic factor for local control. [15] However, in the present study postponement of RT for 5 days or longer was an independent prognostic factor for 3-year overall survival. This factor was not effective on local control, and disease-free survival.…”
Section: Journal Of Medical Updatescontrasting
confidence: 45%
See 1 more Smart Citation
“…[32] McCloskey et al demonstrated that one week deferral of RT in 78 patients with head and neck cancers was an independent prognostic factor for local control. [15] However, in the present study postponement of RT for 5 days or longer was an independent prognostic factor for 3-year overall survival. This factor was not effective on local control, and disease-free survival.…”
Section: Journal Of Medical Updatescontrasting
confidence: 45%
“…[14] McCloskey et al reported that relatively lower pretreatment hemoglobin level (<12 g/dL) in 78 head and neck cancer patients under definitive CRT is an independent prognostic factor for local disease control. [15] In our study hemoglobin levels below 12 g/dL effected 3-year overall, and disease-free survival rates without any impact on local disease control rates. At the same time, lower hemoglobin values had an independent prognostic effect on overall and disease-free survival.…”
Section: Journal Of Medical Updatesmentioning
confidence: 85%
“…However, most patients who are treated with CRT for advanced head and neck cancer suffer from its side effects such as dysphagia, mucositis, xerostomia and nausea. Severe oropharyngeal mucositis leads to decreased oral food intake, resulting in interruption of CRT that may reduce its efficacy (1,2). Nasogastoric tube (NGT) is often placed as enteral nutritional support for head and neck cancer patients with CRT-induced mucositis.…”
Section: Introductionmentioning
confidence: 99%
“…3 We found that total treatment time and baseline hemoglobin level were significant predictors for locoregional failure.…”
mentioning
confidence: 69%